A política pública educacional de Simón Rodríguez para Peru e Bolívia (1824-1854) - Ageu Quintino Mazilão Filho (2017)
In this thesis, the research subject is the public education policy proposed and experienced by Simón Rodríguez, when he took office of Diretor General de Enseñanza Pública, position equivalent to Minister of Education, during the governments of Bolivar e Sucre in Peru and Bolivia, between 1825 and 1826. At this moment, Bolívar was simultaneously president of the republics of Bolivia, Grã-Colômbia and dictator of republic of Peru. On the other hand, during the high point of his brief political career, Simón Rodríguez organized the educational policies in Peru and Bolivia. The objective is to set up a historiographical narrative of the formerly listed process, emphasizing the opponents and supporters of the Rodriguezs policy and the reasons that led to its disapproval by the president Sucre. The chronology includes the period between 1824, when Rodriguez settled in Bogota and opened a public house industry, and 1854, the year of his death, a fact that ends the narrative. Despite its undeniable importance for the biography of Rodriguez and the first public education policies in Latin America, in the context of the Age of Revolutions, research on the subject is still scarce. The educational legislation enacted at this time reflected the nature of Rodríguez's ideas, which were developed during his exile in Europe and influenced by the values of the French Illustration. One of the most important points of these educational reforms was its anticlerical and secularizing aspect. The majority of the clergys patrimony, such as lace and convents, was transferred to the financing of public education and the establishment of primary schools, colleges, hospitals and hospices. Faced with the loss of material goods and the monopoly of the still scarce education, the conservative groups formed a resistance that prevented the implementation of the Rodriguezs educational policy. The political opposition of the high circles of the clergy and the judiciary influenced the decision of the Bolivias president, marshal Sucre. The president considered the costs of establishments and its employers too high, disapproved Rodriguezs measures and motivated his resignation from the position after reprehend him in public. Another key issue for the present work concerns the educational ideas of Rodriguez, analyzed in the light of Intellectual History. From an approach that privileges the dialogue between political, social and cultural dimensions, it is sought to understand Rodríguez's popular education project, constructed from the notions of social school and social education. These two key ideas were at the basis of the prototype of the Republic itself, in which the social education would form a public opinion adept of the republican values. In short, the population knew in school practice the advantages of the republican form over the monarchical government and the social school would forge a republican sensibility